2013
DOI: 10.1158/0008-5472.can-12-4184
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD20 Antibody Promotes Cancer Escape via Enrichment of Tumor-Evoked Regulatory B Cells Expressing Low Levels of CD20 and CD137L

Abstract: The possible therapeutic benefits of B-cell depletion in combating tumoral immune escape have been debated. In support of this concept, metastasis of highly aggressive 4T1 breast cancer cells in mice can be abrogated by inactivation of tumor-evoked regulatory B cells (tBregs). Here we report the unexpected finding that B-cell depletion by CD20 antibody will greatly enhance cancer progression and metastasis. Both murine and human tBregs express low levels of CD20 and, as such, anti-CD20 mostly enriches for thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(132 citation statements)
references
References 52 publications
6
126
0
Order By: Relevance
“…Aging mammals accumulate 4-1BBL 1 B cells and GrB 1 CD8 1 T cells Given its importance in CD8 1 T-cell induction, [22][23][24] and that B cells can elicit antitumor GrB 1 CD8 1 T cells using 4-1BBL, 21 we hypothesized that 4-1BBL 1 B cells could also be responsible for the age-associated expansion of CD8 1 CD28 Low T cells expressing GrB. 10 To test this idea, the 2 cell types were evaluated in the PB of old (79 6 6 years) and young (42 6 9 years) healthy humans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging mammals accumulate 4-1BBL 1 B cells and GrB 1 CD8 1 T cells Given its importance in CD8 1 T-cell induction, [22][23][24] and that B cells can elicit antitumor GrB 1 CD8 1 T cells using 4-1BBL, 21 we hypothesized that 4-1BBL 1 B cells could also be responsible for the age-associated expansion of CD8 1 CD28 Low T cells expressing GrB. 10 To test this idea, the 2 cell types were evaluated in the PB of old (79 6 6 years) and young (42 6 9 years) healthy humans.…”
Section: Resultsmentioning
confidence: 99%
“…20 We recently found that antitumor effector GrB 1 CD8 1 T cells can also be induced when tumorsupporting regulatory B cells (Bregs) are rendered into activators expressing 4-1BBL. 21 Here, given the importance of 4-1BBL in CD8 1 T-cell induction [22][23][24] and the pathogenic role of B cells in autoimmune disorders, 25,26 we hypothesized that the accumulation of 4-1BBL 1 B cells could be responsible for the expansion of GrB 1 CD8 1 T cells in the elderly. To test this idea, we evaluated 4-1BBL 1 B cells and GrB 1 CD8 1 T cells in mammals, such as in healthy human participants of the Baltimore Longitudinal Study of Aging (BLSA), rhesus macaques, and mice.…”
Section: Introductionmentioning
confidence: 99%
“…CXCL13, known as B lymphocyte chemoattractant (BCL), was frequently found in the interaction between cancer cells and B cells [55]. RORγt+ group 3 innate lymphoid also stimulated the expression of CXCL13 by stromal cells in the microenvironment and largely contributed to lymph node metastases [56].…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to how CD20 low 4-1BBL 1 B-regulatory cells regulate Granzyme B expression in CD8 1 T cells. 22,23 Although Granzyme B expression in CD8 1 T cells was found to be increased in follicular lymphoma patients at diagnosis, which was associated with better prognosis, it appeared unchanged in patients with ITP. 21,24 Taken together, our results suggest that in vivo Bdep therapy interferes with in vitro IL-2-dependent CD8…”
Section: Resultsmentioning
confidence: 99%